Starch- and PLA-Based Biocomposites: Interactions with Water (2018)
ABSTRACT: Interactions with water of cassava starch-PLA films, containing glycerol as a plasticiser, coffee husk (CH) fibres as filler and epoxidised soybean oil (ESO) as compatibilizing agent were studied. Films were obtained by extrusion and compression moulding. The hydrophilic character of starch-based films was reduced by the addition of PLA and ESO. Wettability of films was diminished with PLA; however, the other components did not affect it. These materials could be a proper alternative to food packaging because of the overcome of some shortcomings of neat starch films, their suitable properties and food compatibility.